Association of Various Forms of Tobacco Consumption with Pre- Malignant and Malignant Conditions of Oral Cavity. - A Retrospective Analytical Study (Global Journal of Medical Research, 2023)
India faces a twofold burden in the form of smoking and smokeless tobacco and is considered the leading capital of tobacco consumption Tobacco contains numerous toxins and carcinogens which are extremely harmful to the human body and may cause oral cancers lung cancers heart disease stroke COPD emphysema etc It is the major cause of morbidity and mortality worldwide and is considered the most significant etiological factor of oral cavity cancers especially oral squamous cell carcinoma Tobacco is even said to have a link with the development of pre malignant conditions of the oral cavity namely leukoplakia erythroplakia oral submoucous fibrosis tobacco pouch keratosis which may progress to developing oral cancers This is a questionnaire based research study conducted in the community health care centres in Chattisgarh with the aim to study the association of pre malignant lesions with tobacco consumption prevalence patterns of pre malignant conditions occurring in the oral cavity in response to various forms of tobacco consumption and the relation of premalignant and malignant conditions of oral cavity among tobacco users